The influence of the wall thermal inertia over a single-phase natural convection loop with internally heated fluids. (22nd October 2016) - Cammi, A.; Luzzi, L.; Pini, A.
Abstract: This paper deals with the influence of the piping material thermal and geometrical properties on the dynamic stability of single-phase natural circulation loops. To this purpose, a semi-analytical approach is developed by adopting the tools provided by the linear analysis. By considering a generic natural circulation loop configuration with a localized heat flux and a homogenously distributed Internal Heat Generation (IHG), the governing equations (mass, momentum and energy balance) are linearized around a steady-state solution of the system and treated by means of the Fourier transform to obtain dimensionless stability maps. Moreover, in order to verify the linear analysis methodology, a numerical strategy is adopted to solve the nonlinear governing equations and to investigate the natural circulation dynamics in the time domain. In principle, both the developed approaches can be applied to any natural circulation loop configuration. In the present work, the linear and the nonlinear analyses are applied to a specific natural circulation loop geometry, namely the Horizontal Heater Horizontal Cooler (HHHC) one. In this regard, an Object-Oriented (O-O) one-dimensional model of the HHHC loop is developed. For the assessment of the O-O model, the obtained results are compared with RELAP5 and Computational-Fluid-Dynamics (CFD) time-dependent simulations. Highlights: Analytical/numerical modelling of piping-material influence on natural circulation dynamics. Piping-material properties affect the stability behaviour of a natural circulation loop (NCL). Frequency analysis highlights the effects induced by different piping materials. 1D simulations are suitable to catch the stable/unstable flow regime of NCLs. For 1D systems an all-external heat flux can mime the distributed internal heat generation.